Methods and Practices for Using AI in Education - Stefanov, Krassen (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
Generative AI and foundation models are reshaping education through new tools, pedagogical methods, and institutional practices. Based on a structured review of recent literature and policy documents, this paper proposes a taxonomy of AI-based educational systems, outlines supported teaching methods, and identifies near-term trends, indicators, and risks.
Keywords: Education; Generative Ai; Foundation Models; AI Literacy; Education Policies